Exploitation of nanoparticle–protein corona for emerging therapeutic and diagnostic applications. Issue 25 (6th June 2016) - Palchetti, S.; Pozzi, D.; Mahmoudi, M.; Caracciolo, G.
Abstract : Exposure of nanoparticles (NPs) to biological fluids ( e.g., plasma, interstitial fluid, and cytoplasm) leads to the absorption of proteins on the NP surface, forming a protein corona (PC) that drastically influences the NP physicochemical properties. Abstract : Exposure of nanoparticles (NPs) to biological fluids ( e.g., plasma, interstitial fluid, and cytoplasm) leads to the absorption of proteins on the NP surface, forming a protein corona (PC) that drastically influences the NP physicochemical properties. Herein, we highlight the emerging applications of PC towards its use in therapeutics and diagnostics. In particular, special emphasis is given to the exploitation of PC for targeted delivery of nanomaterials and early cancer detection. By highlighting such recent applications of PC, we hope to demonstrate that this bio-entity has the potential to determine the success of NPs in biomedicine beyond their currently envisioned purposes.